Comparative study of stress responses, laterality and familiarity recognition between albino and pigmented fish - Slavík, Ondřej; Horký, Pavel; Valchářová, Tereza; Pfauserová, Nikola; Velíšek, Josef (Zoology (Jena, Germany), 2022)
Oculocutaneous albinism is the result of a combination of homozygous recessive mutations that block the synthesis of the tyrosine and melatonin hormones. This disability is associated with physiological limitations, e.g., visual impairment expressed by lower visual acuity and movement perception, and eventually leads to acrophobia and/or photophobia, suggesting a potentially higher stress level associated with the behavioral responses of individuals with albinism to external stimuli compared to their pigmented conspecifics. However, in fish, differences in behavioral and/or physiological responses and stress levels between these phenotypes have been poorly documented. While acoustic perception of albino individuals is well known, the use of olfactory sensors for social communication, e.g., for the preference for familiar conspecifics, remains poorly understood. We performed two laboratory experiments with albino and pigmented European catfish Silurus glanis to observe: i) their behavioral and physiological responses to short-term stress induced by a combination of air exposure and novel environmental stressors and ii) their ability to use odor keys to recognize of familiar conspecifics and the influence of lateralization on this preference. In response to stress stimuli, albino fish showed higher movement activities and ventilatory frequencies and more often changed their swimming directions compared to their pigmented conspecifics. Blood plasma analysis showed significantly higher values of stress-, deprivation-, and emotional arousal-associated substances, e.g., glucose and lactate, as well as of substances released during intensive muscle activity of hyperventilation and tissue hypoxia, e.g., hemoglobin, mean corpuscular hemoglobin, erythrocytes, and neutrophil granulocytes. A preference test between environments with and without scented water showed the preference by both albino and pigmented catfish for environments with scent of familiar conspecifics, and both groups of fish displayed left-side lateralization associated with the observation of conspecifics and group coordination. The results tended to show higher physiological and behavioral responses of albinos to stress stimuli compared to the responses of their pigmented conspecifics, but the uses of olfactory sensors and lateralization were not differentiated between the two groups.
Keywords: Catfishes; movement activity; Albinism; fobie; rozpoznávání (psychologie); preference test; Animals; plavání; blood plasma; sumci; Recognition, Psychology; fish; ventilatory; zvířata; albinismus; albinism; Swimming; Phobic Disorders; frequency